Where do students rest in MacEwan University - Kamau, Terence (My University, 2018)
In University/College institutions, napping is a common occurrence and practice used by students to alleviate daytime sleepiness. Sleep debt up to 17 to 19 hours is on par with a drunk individual having a blood alcohol content (BAC) of 0.05 (two wine glasses), whereas most states have the BAC limit at 0.08; 0.04 for commercial drivers. Napping stops the symptoms, where there’s too little time to cure the disease. MacEwan University will be observed for nap proportions of students napping on furniture, to the proportion of total seats taken in the same area. Data was collected twice a day (once Monday) on the weekday, for 7 days. Areas were observed for an hour interval, at four different times. Furniture seating was counted through furniture design. Five areas were observed for 10-minute periods for napping individuals and total seats occupied. Sex of the individual presumed male, presumed female, ambiguous was observed. Sound level of each area was recorded by a sound app for a one-minute interval. Area description will account for furniture differences for suitability of napping area. A binary logistic regression was used to analyze the data, which showed location and time as significant to where people sat (p-value<0.05).
Presented on April 23, 2018 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: post secondary education; sleep; napping; students